Leadership in Communities Beyond Formal Structure: The Case of Kampung Cakrawala, Semarang,Indonesia - As Sifa Putri Damayanti; Kuncoro Bayu Prasetyo (UNIB Press, 2026)
Kampung Cakrawala is an informal settlement in Semarang City without formal institutional structures or legally recognized leadership, which limits residents’ access to administrative and social services. This study examines the dynamics and challenges of leadership within the Kampung Cakrawala paguyuban, addressing the limited research on leadership in settlements outside formal institutions. Using an ethnographic approach through participant observation and in-depth interviews, the study finds that the paguyuban leader functions as a coordinator, conflict mediator, and liaison with external parties. Drawing on Victor Turner’s concept of liminality, the findings show that the kampung’s “titipan” status creates administrative ambiguity that shapes leadership patterns and social life. In this context, the paguyuban leader performs roles similar to those of a neighbourhood unit (RT), exercising flexible, trust-based leadership without formal legitimacy. The study concludes that leadership in Kampung Cakrawala represents a form of collective adaptation within a liminal condition, characterized by egalitarian social relations and a combination of spontaneous and normative community forms.